2023
DOI: 10.3390/life13020350
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Induced Coagulopathy: An Update on Pathophysiology, Biomarkers, and Current Guidelines

Abstract: Significant cross talk occurs between inflammation and coagulation. Thus, coagulopathy is common in sepsis, potentially aggravating the prognosis. Initially, septic patients tend to exhibit a prothrombotic state through extrinsic pathway activation, cytokine-induced coagulation amplification, anticoagulant pathways suppression, and fibrinolysis impairment. In late sepsis stages, with the establishment of disseminated intravascular coagulation (DIC), hypocoagulability ensues. Traditional laboratory findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 102 publications
0
42
0
2
Order By: Relevance
“…The overlap of these two systems is attributed to a common pathway; the interaction of the vascular endothelium with platelets and neutrophils. 17 Hemostatic derangements are common and sometimes life-threatening through sepsis progress in neonates. Recent studies showed that ROTEM is able to detect sepsis-evoked alterations of hemostasis and could be used as an early indicator of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The overlap of these two systems is attributed to a common pathway; the interaction of the vascular endothelium with platelets and neutrophils. 17 Hemostatic derangements are common and sometimes life-threatening through sepsis progress in neonates. Recent studies showed that ROTEM is able to detect sepsis-evoked alterations of hemostasis and could be used as an early indicator of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…I nfection is associated with a prothrombotic state due to several pathogenetic mechanisms including extrinsic pathway activation, cytokine-induced coagulation amplification, and fibrinolysis inhibition 7,[16][17][18][19] . The aim of this pilot study was to evaluate the association between hemostatic derangements, as reflected by ROTEM parameters, and the development of PJI.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting material provided by the authors is posted with the online version of this article as a data supplement at jbjs.org (http://links.lww.com/JBJS/H739). n Andreas G. Tsantes, MD 1,2 Dimitrios V. Papadopoulos, MD 3 Stavros Goumenos, MD 4 Ioannis G. Trikoupis, MD 4 Konstantina A. Tsante 5 Vanesa Bellou, MD 6,7 Panagiotis Koulouvaris, MD 4 Dimitra Houhoula 1 Anastasios Kriebardis 5 Daniele Piovani 8,9 Georgios K. Nikolopoulos 10 Andreas F. Mavrogenis, MD 4 Panayiotis J. Papagelopoulos, MD 4 Stefanos Bonovas, MD 8,9 Argirios E. Tsantes, MD 1…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no definitive treatment for SIC. However, considering that the main manifestations of SIC are enhanced coagulation function, anticoagulant inhibition, and microthrombosis, some studies recommended the use of anticoagulant drugs in these patients, although it remains controversial (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%